Reconstruction of Sharia Economic System in Indonesia in Sharia Banking - Wulandari, Elsa Dwi; Arishandy, Mulya Andana; Imtiyaz, Nakhwah Bahirotul (Journal of Finance, Economics and Business, 2024)
This article discusses the reconstruction of the Islamic economic system in Indonesia, particularly in the sector of Islamic banking. The Indonesian government has taken significant steps to support the development of Islamic banking, ranging from the phase of Islamic value freedom to specific regulations. Despite its rapid growth, Islamic banking still faces challenges, especially in the implementation of murabahah financing contracts. The article also highlights government policies aimed at enhancing the role of Islamic banking and adapting to economic and technological changes. The strategic transformation of Islamic banking into the digital realm is considered essential to meet customer needs with a focus on satisfaction. The implementation of policies, including credit relaxation for Small and Medium Enterprises (SMEs), is part of the government's efforts to support the economy through Islamic banking. The development roadmap for 2020-2025 emphasizes the creation of an efficient and contributive Islamic banking system to the national economy. This article provides a comprehensive overview of the restructuring of Islamic banking in Indonesia through a literature research approach, emphasizing the government's role, addressing challenges, stimulating digital innovation, and implementing policies for the sustainable development of Islamic banking